2015
DOI: 10.1039/c4cp04966g
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of a hydrophilic polymer induced by moisture desorption through the glass transition

Abstract: Regarding the underlying special relaxation feature of a water-plasticized hydrophilic polymer during performance evolution with water content change, we report the water desorption kinetics and periodic creep responses of poly(vinyl alcohol) (PVA) films subsequent to rejuvenation by above-glass transition relative humidity (RH) annealing and following RH-jump at various rates. A Moisture Sorption Analyzer and a Dynamic Mechanical Analyzer are utilized to control RH and to capture data to probe the evolving re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…PET is defined as a hydrophobic polyester because it sorbs less than 1% water (g/g dry), as in the curve [ 53 ]. For this reason, not many studies have been carried out to understand the sorption and diffusion of water molecules onto PET, since the majority of authors have observed a linear behavior of the water content in PET at an established relative humidity (RH) (sorption/diffusion) [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…PET is defined as a hydrophobic polyester because it sorbs less than 1% water (g/g dry), as in the curve [ 53 ]. For this reason, not many studies have been carried out to understand the sorption and diffusion of water molecules onto PET, since the majority of authors have observed a linear behavior of the water content in PET at an established relative humidity (RH) (sorption/diffusion) [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the existing equations in Section 2 are also theoretically applicable to describe the aging performance of polymeric glass in vapor environments. For this application, how to specify the aging parameters would be critical, as the glass transition temperature is primarily influenced by the moisture concentration [45].…”
Section: Discussionmentioning
confidence: 99%
“…3B). The film deformed much faster; above 75 1C, the curling was completed in less than 3 s, and at 105 1C, in less than 0.5 s. This rapid mechanical response is ascribed to the concomitant action of two processes-fast contraction of the PVA/Ficoll layer 40 and fast expansion of the PVDF/AAB layer. 41 The bilayer strip also curls up on a moist filter paper or in water; however, the hygroinduced motion due to swelling of the PVA/Ficoll layer is much slower than the thermomechanical one.…”
mentioning
confidence: 94%
“…S10, ESI †). [40][41][42][43] The PVA/Ficoll layer is composed of strongly hygroscopic materials that can spontaneously absorb water from the surroundings (Fig. S10A, ESI †).…”
mentioning
confidence: 99%